The management of construction waste: A case study of a housing developer in Kedah - Mohd Sa’i, Nur Khairiyah Na’ilah; Hashim, Rushanim; Omar, Salmah (Universiti Utara Malaysia, 2019)
The aims of this paper are, first, to identify the types of waste of building materials generated from construction site; second, to investigate the factors that cause construction waste to occur in construction site; and third, to investigate the waste management practice used at construction site. This study used qualitative method where the information is obtained from an interview with a project manager from the company being studied. This study reveals that timber, steel, bricks, and wrapping plastics are waste materials that generated from construction projects. Poor management, workers’ mistakes during construction and problems in handling materials can contribute to the generation of construction waste. Normally, timber will be burned to be disposed, while steel will be collected and stored for selling purpose. Besides, bricks waste can be used to build contemporary drainage at construction site. In order to handle and manage waste effectively, firm need to emphasize on workers’ discipline and try to improve the team management on site. A special recycling company that have an authority to collect construction waste should be set up by the government to reduce the waste problem on site.